Effects of the Differences Between FASB and IASB Accounting Policy for Leases - Santana, Verônica de Fátima; Serafim, Jandirson Dutra (Advances in Scientific and Applied Accounting, 2024)
Objective: This research investigates the effects of the 2019 US lease standards for US lessee companies, comparing with the potential effects of IFRS 16 to explore the economic reasons that would have led the FASB and the IASB to diverge from their joint lease standard project. Method: We hand-collected detailed data on leases for 500 US lessees firms’ 2019 financial statements to first analyze Topic 842’s effects on financial ratios and to simulate these effects had the FASB adopted the same earnings recognition criteria in IFRS 16. Next, we investigate the value relevance of these observed and simulated effects on the stock market. Results: Topic 842 generated significant variations in companies' financial indicators, but it was not possible to identify the value relevance of these variations due to model limitations. The IFRS 16 simulation shows a significant increase in EBIT and operating cash flows, but a drop in net income, which seems to have been incorporated into stock prices. This suggests the FASB’s decision to diverge from the IASB could include the desire to avoid lower earnings and their negative impacts on the stock market. Contributions: This research adds to the literature first by focusing on the US when most of the recent studies investigated the IFRS world and, second, by exploring economic reasons rather than the hierarchy of power between the FASB and the IASB. Finally, we add a novelty derived from the detailed manual work which allowed us to estimate the effects had the US firms been under IASB’s jurisdiction.